Characterization of Ralstonia solanacearum causing bacterial wilt in ginger - Y.R. SARMA, A. KUMAR* and (Indian Phytopathology, 2004)
Bacterial wilt pathogen Ralstonia solanacearum isolated from ginger, tomato, Chromolaena, chilli and potato, characterized for biovar, pathogenicity, infectivity titer, and intrinsic antibiotic resistance. The isolates were also characterized on the basis of their membrane protein pattern and amenability of the isolates for serological detection (NCM-ELISA) using R. solanacearum specific antibodies. All the ginger isolates were highly fluidal with characteristic spiral pink center on 2,3,5-triphenyl tetrazolium chlorideamended medium. Among the isolates characterized nine belongs to biovar 3 while one from potato to biovar 2. Among the various isolates tested, only ginger ones except one from Assam induced cent percent wilting in ginger cv. Himachal within a week. Plants were wilted even at a concentration of 3.2 X 102 cfu ml- 1 in stem inoculation while in soil inoculation it was 105 cfu ml- 1 . All the isolates were resistant to antibiotics tetracycline, polymyxin B sulphate and chloramphenicol and isolates GRS Tms and its spontaneous mutant were resistant to Rifamycin. Isolates were detected with NCM-ELISA and biovars on the basis of membrane protein pattern on SDS-PAGE and biovar specific protein from R. solanacearum could be isolated.